(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It is essential to make the public aware of formidable consequences of Environmental Degradation. We are facing various environmental challenges. It is essential to get or students acquainted with these challenges that their act may be eco-friendly. The vast majority of our population our directly dependent on nature resources for their basic needs of food, fuel shelter and fodder. Thus the challenge of poverty is the challenge of environment. So our population must be acquainted with methods to sustain and increase agricultural growth with damaging environment. Nearly 27 Indian live in urban areas. Urbanisation Industrialization has given birth to a great number of environmental problem that need urgent attention. So there become popular issue to make our students aware of this growing the pollution, so this is also important to informed our public about environmental programs and movement. The researcher twits that the environmental education helps at developing awareness and knowledge about environment issues and help them to develop positive attitude and skills in this regard. Environmental studies deals with every issue that affects an organism. So it becomes very important to make students to aware these.